(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The paper tests the effects of attitude, subjective norm and the quality of information about Islamic insurance demand. Inspired by the theory of reasoned action (TRA), this study proposes a model to examine the factors in the Islamic context of the application of insurance. The model is tested using data from a survey of 100 respondents. The results suggest that attitude, subjective norm and the quality of information available should be considered essential in determining the demand for Islamic insurance factors. The results of this study highlight the level of consumer acceptance of Islamic insurance. It also provides valuable information for operators to manage Takaful Islamic insurance services effectively.